Case Report: A rare hyperplastic polyp with synchronous high-grade intraepithelial neoplasia in both glandular and squamous epithelium in autoimmune gastritis - Zhang, Dian; Chen, Xueqin; Hendi, Maher; Tang, Wen; Tan, Chenfei; Liu, Juan; Hu, Weiling (Frontiers in Oncology, 2025)
A 68-year-old man came to evaluate a gastric polyp discovered during a routine gastroscopy. After endoscopic mucosal resection, pathological findings confirmed that it’s a hyperplastic polyp. Notably, squamous metaplasia was observed within the hyperplastic polyp, and both squamous and glandular epithelium exhibited high-grade intraepithelial neoplasia. Besides, the diagnosis of autoimmune gastritis was established by comprehensive assessment including gastric endoscopic findings, histopathological examination and serological studies. The patient experienced no postoperative discomfort and had oral medication for two weeks. In this paper, we presents a first case worldwide of hyperplastic polyp with synchronous high-grade intraepithelial neoplasia in both glandular and squamous epithelium in autoimmune gastritist. In previous cases, the occurrence of hyperplastic polyps with neoplastic transformations or squamous metaplasia is very rare, but what we found this time was the concurrance of both lesions on hyperplastic polyps. This extremely rare case not only provides further clinical evidence for the metaplasia and neoplastic transformation potential of hyperplastic polyps, but also highlights the necessity of regular follow-up examination for autoimmune gastritis - a well-established precancerous condition.